Knowledge Engineering and Knowledge Management 18th International Conference, EKAW 2012, Galway City, Ireland, October 8-12, 2012, Proceedings - ten Teije, Annette; Völker, Johanna; Handschuh, Siegfried; Stuckenschmidt, Heiner; d'Acquin, Mathieu; Nikolov, Andriy; Aussenac-Gilles, Nathalie; Hernandez, Nathalie (Lecture Notes in Artificial Intelligence, 2012)
This book constitutes the refereed proceedings of the 18th International Conference on Knowledge Engineering and Knowledge Management, EKAW 2012, held in Galway City, Ireland, in October 2012. The 44 revised full papers were carefully reviewed and selected from 107 submissions. The papers are organized in topical sections on knowledge extraction and enrichment, natural language processing, linked data, ontology engineering and evaluation, social and cognitive aspects of knowledge representation, application of knowledge engineering, and demonstrations.